Synonym based malay linguistic text steganography - Muhammad H.Z.; Shakil A.; Syed Ahmad Abdul Rahman S.M. (2023)
This paper describes a Malay linguistic text steganography system which is capable of hiding a secret message into Bahasa Melayu cover text which can only be detected by intended recipients whilst avoiding suspicions from others. The steganography algorithm is based on synonym based substitution which exploits the simplicity of Bahasa Melayu's grammar rules. The syntax and semantic structures of the resulting Bahasa Melayu stego-text is well preserved so that it appears innocuous to human reader. This paper describes in detail the steganography algorithm that involves the encryption and decryption processes, its advantages and limitations. 2009 IEEE.